KONSEP OTONOMI DESA DALAM PENYELESAIAN SENGKETA PEMILIHAN KEPALA DESA (BERDASARKAN PERATURAN BUPATI SUMENEP NOMOR 54 TAHUN 2019 TENTANG PENCALONAN, PEMILIHAN, PENGANGKATAN, PELANTIKAN DAN PEMBERHENTIAN KEPALA DESA DENGAN PERDA KABUPATEN SUMENEP NOMOR 3 TAHUN 2019 TENTANG DESA - Akh Wardi (Universitas Muhammadiyah Jember, 2021)
This research is a normative type of research carried out with a legal and historical problem approach so that with prescriptive analysis a discussion can be found as an answer to the problems in regulating village head elections in relation to village administration as a form of village autonomy. One important aspect of Village governance is the aspect of village head elections. Therefore, in the formation of regulating village heads, of course, must pay attention to village autonomy authority. The existence of conflicting norms in the Regulation of the Regent of Sumenep Number 54 of 2019 (Article 26 paragraph (1) number 3 and paragraph Article 26 paragraph (2)) with the Regional Regulation of Sumenep Regency Number 3 of 2019 (Article 16 and 17 letter (a)) shows that Village administration has a very important position and has full authority, especially in producing rules regarding village head elections.